Virginia Woolf, Fashion and Literary Modernity. - Koppen, R. S. (Edinburgh University Press, 2009)
Virginia Woolf, Fashion and Literary Modernity places Woolfs writing in the context of sartorial practice from the Victorian period to the 1930s, and theories of dress and fashion from Thomas Carlyle to Walter Benjamin, Wyndham Lewis and J.C. Flugel. Bringing together studies in fashion, body culture and modernism, the book explores the modern fascination with sartorial fashion as well as with clothes as objects, signs, things, and embodied practice. Fashion was deeply implicated with the nineteenth-century modern and remained in focus for the modernities that continued to be proclaimed in the.